Why do North African firms involve in corruption? - (:unkn) unknown (My University, 2007)
This paper empirically analyzes the main microeconomic determinants of different forms of corruption supply. Our study is based on a new database of near 600 Algerian, Moroccan and Tunisian firms. We show that the undeclared part of firms' sales is a major factor of their involvement in administrative corruption. The latter increases with the part of the firm's informal activity as far as it is inferior to 55% of total sales, before slightly decreasing. State capture is rather strengthened by a failing enforcement of property and contract rights. Moreover, both forms of corruption help to compensate a loss of competitiveness, which contradicts previous results on this issue. Finally, we draw a comparison of the factors of corruption in North Africa, Uganda and transition countries and derive policy recommendations.
Keywords: African Research